Prediction of Vessel Traffic Volume in Ports Based on Improved Fuzzy Neural Network - Guilian Su (IEEE Access, 2020)
The accurate prediction of vessel traffic volume (VTV) is very helpful to rational scheduling of port resources and reducing vessel accidents. However, the traditional VTV prediction methods face problems like the overfitting of historical data and prediction inaccuracy. To solve these problems, this paper improved the fuzzy neural network (FNN) with quantum genetic algorithm (QGA). Firstly, the basic principles of neural network (NN), fuzzy inference and the QGA were introduced in turn. Then, the weights of the FNN were optimized by the QGA. On this basis, the authors established a VTV prediction model based on the improved FNN. Finally, the established model was applied to predict the VTV in an actual port of China, in comparison with several classic NNs. The VTV data were collected based on the length and gross tonnage of vessels. The results show that the improved FNN outperformed the contrastive methods in the accuracy of VTV prediction, thanks to the optimization by the QGA. The proposed method enjoys a great application potential in the prediction of the VTV in ports.